The Role of The WTO In Responding To International Trade Issues - Dodi Sugianto (Journal Research of Social Science, Economics, and Management, 2023)
The World Trade Organization, also known as the WTO, is a global organization that specifically oversees international trade. The World Trade Organization (WTO) was founded to realize fair dispute resolution and more orderly, smooth, free, liberal, transparent, and predictive global trade. The signing of various agreements among WTO member states on international trade regulations marked the achievement of the organization's goals. Here are the objectives of this study: 1) Studying international trade issues; 2) Understanding the role of the World Trade Organization (WTO) in addressing issues relating to international trade. To fully explain the research topic, qualitative research is used to describe and analyze it. Relevant literature such as books, journals, term papers, and articles are used in research, such as the internet. The study found that international trade issues can be broken down into six categories, namely as follows: 1) Technical preparation, 2) State security, 3) Export and import implementation policies, 4) Product preparation, 5) Lack of trust, and 6) Connections with international organizations Trade barriers can be removed by the WTO to protect consumers, stop the spread of disease, or preserve the environment to solve these problems.